University Teacher training: from rationalisation to positing the problem (Praxis Educativa, 2012)
Acknowledging that school is not what it used to be and it is not for the people it used to be, the discussion at university level is centred on a false dichotomy: knowledge and experience. This dichotomy is in most cases based on beliefs and not on knowledge resulting from situated research. It is our aim to make a suggestion to the debate emanating from INFOD’s proposal as our one decade knowledge fully represents a famous assertion attributed by students to honour L. Stenhouse: only by understanding it, would teachers be able to change school. And understanding does not come from applied knowledge; nor does it come from experience. It originates in praxis. As teacher-trainers, we are socially responsible for the professionals we train. Their commitment should be to battle exclusion.
Keywords: teacher-training; research; understanding; exclusion